Mass transport analysis for tritium removal in FHRs. (November 2018) - Wu, Xiao; Shi, Shanbin; Zhang, Sheng; Arcilesi, David; Christensen, Richard; Sabharwall, Piyush; Sun, Xiaodong
Highlights: A Logarithmic Mean Square root of Partial Pressure Difference (LMSPD) method is developed for a cross-flow tritium removal facility designed for tritium control in FHRs and benchmarked against a hydrogen permeation experiment. An overall mass transfer code based on the LMSPD method is developed and applied to a cross-flow tritium removal facility. Parametric study of the cross-flow tritium removal facility is performed, confirming the salt and sweep gas flow rates and inlet T2 concentration are the key factors affecting the facility performance. Abstract: Tritium control and mitigation is one of the most significant issues in Fluoride Salt-cooled High-temperature Reactors (FHRs). To address this issue, a cross-flow tritium removal facility has been proposed to remove molecular tritium, T2, from the primary coolant. To model the performance of the design, a method is developed based on the logarithmic mean difference of the square root of the tritium partial pressures on the upstream side and the purging gas side. A computer code has been developed based on this global analysis method to study the effectiveness of tritium removal in such a cross-flow tritium removal facility. The code is benchmarked against experimental data from a hydrogen separation experiment in the literature and compared with the results from a code based on traditional finite volume method. Evaluation of the cross-flow tritium removal facility designed for FHR systems has also been performed. The results show how the key factors, i.e., the fluid flow rates and tritium inlet concentration affect the performance of the facility.